STUDI PENGGUNAAN LIMBAH SERBUK KACA SEBAGAI BAHAN SUBSTITUSI SEMEN PADA PEMBUATAN BATA BETON PEJAL - Indah Handayasari; Gita Puspa Artiani; Desi Putri (FORUM MEKANIKA, 2016)
Waste glass is often the trash unused and potentially damaging to the environment because it is difficultto decompose. Though glass waste has the potential to be used, one of them as a substitute for cement inconcrete solid brick. The purpose of this study was to determine how much influence the addition of glasspowder waste of compressive strength of concrete solid brick. Manufacture of solid concrete brick made fromwaste fine aggregate, cement PC type I, and glass powder from waste glass bottles. Test object of research ismade with a composition ratio of cement, fine aggregate and water with glass powder 4 substitution treatmentwere 0%, 10%, 20%, and 30% by weight of cement. Compressive strength testing is done on day 7,14, 21 and28. From the test results obtained optimum compressive strength value contained in glass powder ratiovariation of 10% of the cement with the compressive strength obtained at 73.33 Kg / cm2 and included intothe Tertiary quality II. This shows the glass powder can be used as an additive in the manufacture of solidconcrete brick so that it can be used as an alternative to environmentally friendly construction materials.